Predictive Power of X-ray Chest Findings in the Diagnosis of Carcinoma Lung - Kaleem Ullah Toori , Ali Zohair Nomani , Maxwell Winson (Journal of Rawalpindi Medical College, 2014)
Background: To define relationship of chest x-ray abnormality with the diagnosis of lung cancer with a view to identify those at high risk of lung cancer. Methods: In this descriptive study patients with suspicion of lung cancer , were included. Chest x-ray findings and final diagnosis of all the patients were recorded. All patients had contrast enhanced chest CT-scan and bronchoscopic evaluation by the chest physician. Patients with peripheral lung lesions had CT guided lung biopsy. Open lung biopsy was organized for patients with lung lesions not approachable bronchoscopically and not suitable for CT-guided lung biopsy. Final diagnosis was recorded and patients were identified as having lung cancer or not on the basis of tissue biopsy. Patients with major systemic diseases including neurological disorders, cardiovascular disease, endocrine and autoimmune disease or diseases related to gastrointestinal, renal, haematological, dermatological or musculoskeletal system were excluded. Results: Out of 701 patients 45% were found to have lung cancer. Univariate analysis demonstrated that mass lesion was significantly more common in lung cancer and findings of normal x-ray, prominent hilum and fibrotic shadow significantly were less common (p<0.05). Multivariate analysis showed mass lesion as strong predictor, and normal chest x-ray and fibrotic shadows as powerful negative predictors of lung cancer (p<0.05). Conclusion: Chest x-ray interpreted by an experienced radiologist as abnormal is neither a sensitive nor a specific tool to predict lung cancer except if a mass lesion is identified